The influence of self-help group therapy towards quality of life of cancer patients in palliative care - Kardiyudiani, Ni K.; Wulandari, Apri N.; Susanti, Brigitta A. D. (International Journal Of Community Medicine And Public Health, 2019)
Background: The therapy of cancer treatment for patient affects the significant of physic, psychology, and information and social, so that it needs to support the adequate care. The supporting for adequate care is the way to improve the quality life of patients. One of the cares that given is self-help group therapy (SHG), it is a group treatment to share about the experiences of each other for cancer patient. This research is conducted to know the influences of self-help group therapy towards the quality of life of cancer patients that have a palliative care. Methods: The research uses a quantitative approach with quasi-experimental method with pre-test and post-test with control group design. The sample of this research is 14 respondents in control group and 14 respondents in intervention group. Results: There was significant difference value of quality of life pre-test rather than post-test in the intervention group, p=0.033, and there was no significant difference in the control group before and after intervention, p=0.190. The comparison between post-test intervention and post-test control group showed that there was significant difference of quality of life value. P value in intervention group was 0.002, while p value for the control group was 0.221. Conclusions: There was influence by giving self-help group (SHG) therapy towards the quality of life of cancer patients that have palliative treatment. The patient can expand the social networking, to accept the information, get the emotional supporting from their own group.